Incremental Selection of Regional Air Quality Measures. Issue 5 (2018) - Carnevale, C.; Guariso, G.; Ferrari, F.; Maffeis, G.; Turrini, E.; Volta, M.L.
Abstract: To comply with EU regulations, local environmental authorities of the regions where the mandatory air quality limits are not met must develop suitable emission reduction plans. These normally represent a compromise among what is economically feasible, what is politically acceptable, and what can provide measurable benefits. As a consequence, they include a large number of different abatement measures pertaining to a wide variety of fields (transport, building, agriculture…), the total effect of which is different from the simple sum of the individual outcome. We illustrate how such a problem has been tackled in an Italian region, supporting the analysis through an integrated modelling tool.